Propagação vegetativa de espécies do gênero Spondias sob diferentes concentrações de ácido indolacético - (:unkn) unknown (Universidade Estadual de Goiás, 2018)
Among the 18 species belonging to the genus Spondias of the family Anacardiaceae, six are tropical fruit trees in domestication, which are exploited by the commercial value of their fruits. The species of this genus have a remarkable agro-economic and social potential for local communities. However, to make these crops viable, there is a need for research to solve technological and propagation problems, which make commercial exploitation impossible. Thus, vegetative propagation by cutting has become one of the most important methods of fruit species, since it conserves the characteristics of the matrix plant transmitting the genetic patrimony and increases its precocity. However, studies are needed to potentiate rooting and sprouting capacity, and the use of growth regulators, mainly auxins, are fundamental for these processes. The objective of this work was to evaluate the effect of different concentrations of indole-3-acetic acid on the vegetative propagation of Spondias dulcis, S. purpurea and S. tuberosa in three immersion times. The experiment was conducted in a greenhouse of the State University of Goiás, Ipameri Campus. In the three experiments, the experimental design was completely causalized, with three replicates, in a factorial scheme, using six concentrations 0, 2, 4, 6, 8 and 10 g L-1 of indole-3-acetic diluted in ethyl alcohol with three different immersion intervals, 8, 16 and 24 seconds, with ten stakes per plot. The experimental period was 180 days, and the percentage of survival of the cuttings, percentage of rooted cuttings, number of cuttings, number of young shoots, general length of roots and fresh total mass. Data were submitted to analysis of variance and, later, adjusted in regression equations. The vegetative propagation in the species Spondias dulcis did not obtain satisfactory results using this technique. However, the vegetative propagation by cuttings in the species Spondias tuberosa and Spondias purpurea were satisfactory, with rooting and sprouting of the cuttings favored in the concentration 10 g L -1 of indole-3-acetic, in the times of 16 and 24 of seconds immersion, respectively
Keywords: Spondias; ácido indolacético; propagação vegetativa; CIENCIAS AGRARIAS